The Globalization of International sSociety - Edited by Dunne, Tim and Reus-Smit, Christian (UK Oxford University Press, 2017)
This volume reconsiders the process of globalization, drawing on a wealth of new perspectives to understand better this momentous historical development.
Include Index and References
Keywords: World politics -- International relations -- Globalization